2007 Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/1-2--2314
|View full text |Cite
|
Sign up to set email alerts
|

Testing Our Assumptions: Mathematics Preparation And Its Role In Engineering Student Success

Abstract: She oversees projects in freshman programs, math support, mentoring, outreach, and women's programs. She earned a B.S.E. degree in Mechanical Engineering from Duke University and a master's degree in journalism from the University of California at Berkeley.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 1 publication
0
25
0
Order By: Relevance
“…However, since many students drop out of engineering, too few engineering students graduate to join industry (Froyd & Ohland, 2005). More specifically, many students drop out of engineering not because they failed an engineering course, but because they failed a mathematics course (Gardner, Pyke, Belcheir, & Schrader, 2007;Hoit & Ohland, 1998;Van Dyken, Benson, & Gerard, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, since many students drop out of engineering, too few engineering students graduate to join industry (Froyd & Ohland, 2005). More specifically, many students drop out of engineering not because they failed an engineering course, but because they failed a mathematics course (Gardner, Pyke, Belcheir, & Schrader, 2007;Hoit & Ohland, 1998;Van Dyken, Benson, & Gerard, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Because of the negative impact of mathematics on graduation rates from engineering (Gardner et al, 2007;Hoit & Ohland, 1998;Van Dyken et al, 2015), we are striving to rigorously document what mathematics knowledge and skills students need to successfully enter their engineering degree programs and inform the dialogue that calls for.…”
Section: Discussionmentioning
confidence: 99%
“…In a detailed statistical study presented elsewhere 11 , we found that the conventional wisdom about mathematics preparation and persistence in engineering programs was simply not supported by the data. In fact we found that placement in first math course (a reasonable measure of mathematical preparation) was not correlated with persistence in engineering at Boise State University.…”
Section: Rethinking Assumptions -A Fundamental Research Processmentioning
confidence: 62%
“…About 70% of students who successfully graduate with engineering degrees at Boise State University begin their first semester in a class below calculus level. 5 Figure 3 also shows that the proportion of students at a given level is smaller than the proportion of students at the earlier level, which is to be expected since a certain amount of attrition occurs at each level. The exception is the senior class, which reflects the fact that the final portion of a program is often spread out due to work and other factors.…”
Section: Students Are Classified According To Academic Progress Through the Engineering Curriculummentioning
confidence: 69%
“…And conversely, poor performance in math was correlated with the student leaving the university. 5 This factor (performance in first math class) was found to be more significant than their original math placement level.…”
Section: Putting the Sieve To Workmentioning
confidence: 93%